Lessons from the Bologna decade - Abd Razak, Dzulkifli (2010)
THE recent Second Ministerial Bologna Policy Forum in Vienna, Austria ended on a positive note. It was participated not only by 47 countries, which are signatory to the Bologna framework for higher education, but also other nonEuropean counterparts such as Malaysia. More significantly, the Forum marked the 10th year of the Bologna Process, which was established in 1999 by a handful of countries in "old" Europe.